Reason in the Qur'an and the Brain in Neuroscience: An Epistemological Reconciliation for Modern Islamic Education - Nofrizal Nofrizal; Yufrizal Yufrizal; Syahruddin Syahruddin; Nurhadi Ahmad; Yanfaunnas Yanfaunnas; Ahamd Lahmi; Julhadi Julhadi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study examines the epistemological reconciliation between the concepts of reason in the Qur'an and the brain in modern neuroscience to develop a paradigm for contemporary Islamic education. As neuroscience increasingly illuminates the biological foundations of cognition, the challenge lies in integrating these findings with the Islamic understanding of reason as the primary instrument of human understanding. This study identifies reason in the Qur'an as a transcendental epistemological faculty that unites cognitive, moral, and spiritual dimensions, aiming at wisdom and God-consciousness, rather than merely a biological function. In contrast, neuroscience views the brain as the biological substrate of cognition through complex neural networks, with neuroplasticity emphasizing the brain's adaptive capacity. The comparative analysis reveals common functional roles in thinking, reflection, and decision-making, while highlighting key epistemological differences: neuroscience explains how cognition occurs, while the Qur'an explains why cognition exists and its ultimate purpose. This study proposes a Qur'anic Neuroepistemology Framework (QNF), which integrates revelation, reason, and the brain to promote holistic Islamic education that develops intellectual, moral, emotional, and spiritual intelligence while bridging the gap between religious knowledge and modern science